The Influence of Teachers' Pedagogical Competence and the Use of Digital Technology on Islamic Education Learning Outcomes in Senior High Schools in East Java - Anizar, Anizar; Pahrijal, Rival; Arini, Rani Eka; Istiarsyah, Istiarsyah; Nurjannah, Siti (Westscience Press, 2026)
This study aims to analyze the influence of teachers’ pedagogical competence and the use of digital technology on Islamic Education learning outcomes in senior high schools in East Java. A quantitative research approach was employed involving 85 student respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using SPSS version 25 through descriptive statistics, validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that teachers’ pedagogical competence has a positive and significant effect on learning outcomes, demonstrating that effective instructional strategies and classroom management contribute to improved student understanding. Similarly, the use of digital technology shows a positive and significant influence, indicating that technology-supported learning enhances student engagement and comprehension. Simultaneous testing reveals that both variables significantly affect Islamic Education learning outcomes with a coefficient of determination (R²) of 0.491, meaning that 49.1% of learning outcomes are explained by these factors. The findings highlight the importance of integrating strong pedagogical competence with effective digital technology utilization to improve learning effectiveness in contemporary Islamic Education.